2018
DOI: 10.1007/s11213-018-9453-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities for Sustainability: Revealing the Systemic Key Factors

Abstract: By applying systems thinking theory to capabilities literature, this paper examines the factors that support the development of dynamic capabilities towards sustainable management. For such, we conducted an in-depth single case study using Soft System Methodology (SSM) in an energy organisation from an emerging economy. Our analysis of the last twenty years of operation revealed that the organisation has developed new ways to change and adapt in a disturbing environment by integrating sustainability into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 39 publications
1
36
0
10
Order By: Relevance
“…Findings show that executives have no common understanding concerning how sustainability is related to their daily business activities [7]. In this view, managers can combine, in the process of sustainability decision-making, external and internal drivers such as ethics, resources and cost savings, employees' shared values, leadership, reputation, market, laws, competition and customers' satisfaction into their strategic decision-making process, in order to make changes in their organizations and formulate a sustainability strategy that increases economic, ecological and social success [7,[36][37][38][39]. For example, Fairfield et al [40] examined how aspects of organizations, context, and decision-making processes can be aligned to influence the implementation and success of sustainability efforts.…”
Section: Concept Analysismentioning
confidence: 99%
“…Findings show that executives have no common understanding concerning how sustainability is related to their daily business activities [7]. In this view, managers can combine, in the process of sustainability decision-making, external and internal drivers such as ethics, resources and cost savings, employees' shared values, leadership, reputation, market, laws, competition and customers' satisfaction into their strategic decision-making process, in order to make changes in their organizations and formulate a sustainability strategy that increases economic, ecological and social success [7,[36][37][38][39]. For example, Fairfield et al [40] examined how aspects of organizations, context, and decision-making processes can be aligned to influence the implementation and success of sustainability efforts.…”
Section: Concept Analysismentioning
confidence: 99%
“…System-level outcomes are macro-level societal or environmental benefits [208]. Several studies identified the system-level outcomes of inter-organizational sustainability learning by discussing how these alliances and partnerships help to address SDGs [5,19,131,176,193,203,209], or previously discussed millennium development goals [210]. For instance, Dzhengiz [203] provided evidence from electric utilities focusing on alliances and partnerships that address SDG 7 and 13.…”
Section: System-level Outcomes: Contribution To Sustainable Developmementioning
confidence: 99%
“…Unfortunately, the resulting variety of operationalizations can easily disorient researchers. Even though it is widely agreed that sustainability should be embedded into organizational capabilities (Amui et al, 2017; Cezarino, Alves, Caldana, & Liboni, 2019; Gelhard & von Delft, 2016), enabling an organization to adapt, change, and innovate toward different sustainability‐related paradigms (Geissdoerfer, Savaget, Bocken, & Hultink, 2017; United Nations, 2015; European Commission, 2015; Borland & Lindgreen, 2013; World Business Council for Sustainable Development [WBCSD], 2010; Garriga & Melé, 2004; Elkington, 1997), most extant studies provide little discussion on the characteristics of the possible operationalizations of these capabilities. For example, there is a lack of debate on whether it is possible to distinguish sustainability‐specific DCs (e.g., “Green Dynamic Capabilities”; Chen & Chang, 2013) from traditional DCs.…”
Section: Introductionmentioning
confidence: 99%